2009
DOI: 10.1007/s10551-009-0079-z
|View full text |Cite
|
Sign up to set email alerts
|

Investigating Stakeholder Theory and Social Capital: CSR in Large Firms and SMEs

Abstract: corporate social responsibility (CSR), idiosyncrasies, small and medium-sized enterprises (SMEs), social capital, stakeholder theory,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

17
419
0
17

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 588 publications
(453 citation statements)
references
References 52 publications
17
419
0
17
Order By: Relevance
“…The specificities of SMEs can thus be considered sources of competitive advantage when managers know how to use them to establish sustainable strategies, which have positive impacts on financial, commercial, and relational aspects (e.g., Arend 2014; Russo and Perrini 2010;Torugsa et al 2012Torugsa et al , 2013. Of course, this is not the case for all SMEs in all situations (Carroll and Shabana 2010;Dixon-Fowler et al 2013;Russo and Perrini 2010).…”
Section: Smes Sd and Performancementioning
confidence: 99%
See 2 more Smart Citations
“…The specificities of SMEs can thus be considered sources of competitive advantage when managers know how to use them to establish sustainable strategies, which have positive impacts on financial, commercial, and relational aspects (e.g., Arend 2014; Russo and Perrini 2010;Torugsa et al 2012Torugsa et al , 2013. Of course, this is not the case for all SMEs in all situations (Carroll and Shabana 2010;Dixon-Fowler et al 2013;Russo and Perrini 2010).…”
Section: Smes Sd and Performancementioning
confidence: 99%
“…Of course, this is not the case for all SMEs in all situations (Carroll and Shabana 2010;Dixon-Fowler et al 2013;Russo and Perrini 2010). However, these competitive advantages serve as economic and strategic justifications that are often used to convince owner-managers that SD is ''good for business.''…”
Section: Smes Sd and Performancementioning
confidence: 99%
See 1 more Smart Citation
“…Stakeholders have been grouped into categories by various authors (Tsoi, 2010;Russo and Perrini, 2009). Mitchell et al (1997) suggested the use of the attributes of power, legitimacy, and urgency to identify the most salient stakeholders of an organisation.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Combining stakeholder power and well-being could bring a better understanding of social responsibility process and impact of the company on its business environment. This is further justified by the fact that the determination of stakeholder categories itself is recognised as being dynamic and dependent on the organisation's context (Russo and Perrini, 2009).…”
Section: Theoretical Frameworkmentioning
confidence: 99%